The association between labor epidural analgesia and postpartum depression: a systematic review and meta-analysis - Marcela Almeida; Katherine A. Kosman; Mark C. Kendall; Gildasio S. De Oliveira (BMC, 2020)
Abstract Background Previous studies have demonstrated that appropriate treatment for postoperative pain can lead to improvement in depressive symptoms, however the association between adequate intrapartum pain control and the development of postpartum depression is not clear. The purpose of the study was to examine the effects of labor epidural analgesia and postpartum depression. Methods We performed a quantitative systematic review in compliance with the PRISMA statement. We conducted a search of PubMed, Embase, the Cochrane Database of Systematic Reviews and Google Scholar databases. The primary outcome was a positive screen of postpartum depression among women who received labor epidural analgesia up to 3 months into the postpartum period. Meta-analysis was performed using the random effect model. Results Of the 148 studies available, 9 studies with 4442 patients were included in the analysis. The use of labor analgesia on positive depression screen compared to control revealed no significant effect, OR (95% CI) of 1.02 (0.62 to 1.66, P = 0.94). Conclusion Based on current literature, the use of epidural analgesia for pain relief during labor doesn't appear to affect the likelihood of postpartum depression. Future studies are warranted to further investigate these findings and identity other possible preventative interventions that reduce postpartum depression.